Identifying Characters Using Transitivity: A Stylistics Study of “I Stand Here Ironing” - Nurhayati Nurhayati (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
The study is about the application of the transitivity system, one of lexico-grammar used in a Systemic Functional Grammar’s theory, to analyze a literary work “I Stand Here Ironing”. Considering that many previous researchers were interested in studying the short story from literary approach, I purpose to give an alternative perspective of tracking the characterization of the main characters using the SFG theory. The data are  the text of    “I Stand Here Ironing” by Tillie Lerner Olsen  (1961). They are analyzed using the concepts of the transitivity system and field  situation. The result shows that the author of the short story used material process more than the other processes to construct that the main characters did activities in the domestic and physical domain. The mental process is used to depict the characters’ feeling and attitude. The relational process is used to characterize the characters explicitly. Related to the socio-cultural context, the analysis comes to the conclusion that the such characterization is constructed to criticize the patriarchal domination in America in the time of publication.Keywords: transitivity system; characterization; field of discourse; feminism literature